Faktor-faktor yang mempengaruhi kinerja organisasi Balai Latihan Kerja (BLK) (Suatu studi perbandingan antara BLK Surakarta dengan BLK Cilacap) - SUKARNO, Bambang Woro (Universitas Gadjah Mada, 1998)
T h e c fmnges irr t h e d e v e l opaent. of i i - d : ~ s t r y a nd t e c h n o l o g y i s v e r y n o r e f a s t a nd r a.pid 8 % c ompared t c t h e d e v e l o p m e n t o f o ur nrcr.npuwer i n I n d o n e s i a . This k i n d o f t r e n d has t he a . b i l i t . y of i n h i b i t i n g t h e n a t i o n a l d e v e l o p m ent p r o c e s s , as w e l l 8 s r e d u c i n g t h e enip?oyment. o p p o r t u nities. B e s i d e s t his, t h e q u a l i t y o f t h e I n d o n e s i a n m anpower is s t i l l r e l a t i v e l y low. T h i s c~;r.rrbe r e f l e c t e d by t h e s tructure of h er m anpower b a s i n g on t h e e d u c a t i o n s ts.tus, w here by t h o s e w i t h l csw e d u c a t i o n levels a r e t h e l nost d cmirra.nt, g roup. Orre o f t h e r e s p o n s i b i l i t i e s o f t he M i n i s t r y o f Mfanpower is t o o vercome t he a bove merrt iorred p roblem t hrough m anpower d e v e l o p m e n t i n t h e v o c a t i o n a l t r a i n in8 c e n t r e s e s t a b l i s h e d u p t h r o u g h o u t I rrdorresi~. U nfortunate. ly, U P t o now, t h e m anpower d e v e l o p m e n t p o l i c y i s of s. s u p p l y - d r i v e n prodel 8.s o pposed t o H. d e a a n d - d r i v e n mode 1 . C o n s e q u e n t l y t his l e a d i n g t o u nemployment t o many o f t h e t r a i n e d arid e d u c a t e d p e o p l e , O r g a n i z a t i o n p e r f o r m a n c e must b e i mproved and r a i s e d This b e i n g t h e c a s e , i t n ecessitates t h a t t he r o l e o f t h e l e a d e r c o r r e s p o n d s t o t he n e e d s a nd s c o p e o f h i s a . u t h o r i t y 8.nd r e s p o n s i b i l i t y . As r egards t o wPr8.t have b een ment i o n e d , t his r esearch has b een d e s i g n e d t o f i n d o ut t h e f a c t o r s which i n f l u e n c e t he p e r f o r m a n c e o f t he Vocational T raining C e n t r e s . The s t u d y hais f o c u s e d o n T he S u r a k a r t s . rrrd C il8.cs.y T r a i r r i n g C e n t r e s w h i c h m e b o t h l o c a t e d a t 8. district level, T h e o b j e c t i v e of t his r esearch i s t o i d e n t i f y t h e f actors w hich i nf lzlence t h e S u r a k a r t a V ocat i ons.1 T r a i n irrg C entres t o b e i n a more b etter p o s i t i o n i n e n a b l i n g i t s p r o d u c t s e mployed, and m akirrg t he coarnrurtity itself tr; p a r t . i c i y a t e i n s h o u l d e r i n g t h e f i n a n c i a l c ost.s o f t h e t r a i n i n g p rogram. This r esearch was d o n e Gaseil o n k m t h s e c o n d a r y arid p r i m a r y d a t a , T h e f i n d i n g s o f t h e r esearch i n d i c a t e t h a t t he m ost dominant f a c t o r w k t i c h i n f l u e r r c e s t he s uccess of t h e p erf o rmance of t h e V o c a t i o n a l T r a . i n i n g C ent.res i n Sur3.ikart.a i s t he s u c c e s s f u l c omrmnication o f t he c e n t r e t o t h e ccmnunity a bout i t s r o l e a nd m i s s i o n , m d t h e c r d a n i z a t i o n environment. W c m n o t i g n o r e t he possibility t h a t t h e e a chieved r e s u l t s c8.n b e r a i s e d i n c 8 s e t he t raining i nstit ut i o n i n quest i o n i n t e s i f i e s its c oord i n a t i on.